Stability of d‐luciferin for bioluminescence to detect gene expression in freely moving mice for long durations. (8th August 2020) - Nakajima, Kanako; Hamada, Kazuko; Ito, Ryoga; Yoshida, Yukina; Sutherland, Kenneth; Ishikawa, Masayori; Ozaki, Michitaka; Shirato, Hiroki; Hamada, Toshiyuki
Abstract: Circadian disturbance of clock gene expression is a risk factor for diseases such as obesity, cancer, and sleep disorders. To study these diseases, it is necessary to monitor and analyze the expression rhythm of clock genes in the whole body for a long duration. The bioluminescent reporter enzyme firefly luciferase and its substrate d ‐luciferin have been used to generate optical signals from tissues in vivo with high sensitivity. However, little information is known about the stability of d ‐luciferin to detect gene expression in living animals for a long duration. In the present study, we examined the stability of a luciferin solution over 21 days. l ‐Luciferin, which is synthesized using racemization of d ‐luciferin, was at high concentrations after 21 days. In addition, we showed that bioluminescence of Period1 ( Per1 ) expression in the liver was significantly decreased compared with the day 1 solution, although locomotor activity rhythm was not affected. These results showed that d ‐luciferin should be applied to the mouse within, at most, 7 days to detect bioluminescence of Per1 gene expression rhythm in vivo. Abstract : Stability of D‐luciferin affect bioluminescence for long recording.